P361 Risk of persistent gastrointestinal inflammation after treatment with immune checkpoint inhibitors. (30th January 2023) - Jeay, M; Carbonnel, F; Robert, C; Bellanger, C; Meyer, A
Abstract: Background: Immune checkpoint inhibitors (ICI) can cause immune-mediated gastrointestinal toxicity, but the long-term persistence of this toxicity is unknown. We aimed to describe the characteristics of patients with gastrointestinal inflammation persisting more than six months after discontinuation of ICI. Methods: We included consecutive patients treated between October 2010 and March 2022 for endoscopic or histological gastrointestinal inflammation persisting at least six months after the last administration of ICI. Results: Among 178 patients treated for a gastrointestinal immune-mediated adverse event during ICI therapy, 14 (8%) patients had chronic lesions persisting more than 6 months after the last ICI administration. The median follow-up time was 13 months after discontinuation of ICI. The most common symptom was watery diarrhea (54%). Ten (77%) patients had colon involvement and three (21%) had ileal involvement. Ten patients (77%) had an inflammatory phenotype, while two (15%) had a penetrating and one had (8%) a stricturing phenotype. All patients had lymphoplasmacytic infiltrate and basal plasmacytosis, and s54%) had crypt distortion. Two (15%) patients underwent surgery and nine (69%) received specific treatment, including five treated with vedolizumab. Among the patients who were followed up for at least one year, endoscopic lesions persisted at 1 year after stopping ICI in 4/6 patients, and at 2 years in 3/4 patients. Conclusion: Eight percent of patients who had gastrointestinal toxicity due to ICI develop chronic inflammatory bowel disease characterized by watery diarrhea, colitis and lymphoplasmacytic infiltrate.